Augmented Reality in Chemistry Education: A Literature Review of Advantages on Learners - Abdul Talib, Corienna; Romainor, Najibulla; Aliyu, Faruku (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Education moves forward together with technology. In recent years, application of modern technology known as Augmented Reality (AR) has significantly shifted the paradigm of learning process in education, including Chemistry education. Many researchers have explored the potential of AR in education. Unfortunately, literatures on its benefits for leaners in Chemistry education are limited and inaccessible. This research-based paper manifests underlying usefulness of AR in teaching and learning process of chemistry education in terms of (i) Mastering chemistry content and (ii) motivation, interest and attitude. The researchers aspired that with the contents of this paper, other researchers and interested parties could use them for their literature and as incentive to improve current available AR software or develop further advance technology program of AR in chemistry.Keywords: augmented reality, chemistry, education, technology, advantages.